ENDOCANNABINOID SYSTEM AND NEUROCARDIOLOGY: IMPACTS ON AUTONOMIC REGULATION AND CARDIOVASCULAR OUTCOMES IN PATIENTS WITH NEUROLOGICAL DISORDERS - Santos, Arthur Junqueira Ferreira; Ferrarezi, Loren; Medeiros, Rodolfo de Oliveira; Consalter, Guilherme de Lúcio; Oliveros, Camila Menon; Almeida, Sofia Leoncini de; Coércio, Sophia Evaristo; Lima, Renato Augusto Paro; Labegalini, Gabriel Baraldi; Casarin, João Victor Cardoso (INTERFERENCE: A JOURNAL OF AUDIO CULTURE, 2025)
This study aimed to examine the influence of the endocannabinoid system (ECS) on autonomic regulation and cardiovascular outcomes in patients with neurological disorders. An Integrative Literature Review (ILR) was conducted across SciELO, LILACS, PubMed, and ScienceDirect databases, covering the period from 2018 to 2025, and including original articles published in Portuguese and English. The synthesis of findings highlighted the distinct roles of CB₁ and CB₂ receptors, whose effects ranged from protective actions to potential risks for autonomic and cardiovascular stability. The CB₂ receptor demonstrated a relevant role in reducing vascular inflammation and protecting against ischemic events, whereas CB₁ was associated both with nitric oxide–mediated hypotensive effects and with episodes of tachycardia and autonomic instability. In the field of neurocardiology, the reviewed studies suggest that the ECS modulates norepinephrine release from sympathetic fibers, directly influencing hemodynamic control. Recent clinical trials reported that cannabidiol (CBD) may lower blood pressure and improve autonomic variability parameters, particularly in hypertensive patients or under stress conditions. However, these findings remain limited by small sample sizes, methodological heterogeneity, and the scarcity of large-scale randomized clinical trials. It is concluded that the ECS represents a promising biological axis for understanding the interface between neurological diseases, autonomic dysfunction, and cardiovascular risk. Nonetheless, further targeted investigations are required to confirm the efficacy and safety of cannabinoid use in specific clinical contexts. The integration of neuroscience, cardiology, and pharmacology may pave the way for innovative therapeutic approaches aimed at preventing cardiovascular complications in neurological patients.